an epistemic attitude: welcome childhood - Oliveira, Paula Ramos de [UNESP]; Badia, Denis Domeneghetti [UNESP] (State Univ Rio De Janeiro, 2020)
Based on Paul Ricoeur's elaborations on the phenomenological project, this text intends to situate and problematize both the reading of suspicion (practiced by explanatory or reductive hermeneutics) and the welcome reading (practiced by understanding or establishing hermeneutics), understanding them as epistemic attitudes that make it possible to conceive childhoods and children in radically different ways. The way chosen here defends the welcome reading as opposed to the reading of suspicion, since explanatory or reductive hermeneutics would look at childhoods and children from an external, superior, objective point of view, objectifying them with the explanations produced; while understanding or establishing hermeneutics are placed in relation to childhood and children - there is someone who looks, but who is also looked at - in an epistemic attitude of understanding and welcoming otherness. The other is everyone who is also another of us. And each of us is not a monolithic, linear, evolutionary, chronological block. We inhabit the world with complexity, depth, intensity and ambivalence. Therefore, we will discuss the views of childhoods and children that these hermeneutics establish and present some contributions from Jorge Larrosa and anthropological studies, especially in the field of children's anthropology, which, when drawing up an inventory of possible alternative ways to exist in the world, highlights the plurality of childhoods, as well as differences in the relationships established between adults and children in different socio-cultural contexts.
Keywords: childhood; children; epistemic atitude; reading of suspicion; welcome reading